The impact of service quality on Malaysian Muslim Islamic bank customers: satisfaction,loyalty and retention - Elmontaser, Mohamed Abubaker; Syed Jaafar Alhabshi, Syed Musa (International Islamic University Malaysia, 2016)
With increasing competition in terms of better services and recent specific requirements for shari’ah compliance, the Islamic banking sector is not only expected to provide a higher standard of quality service, but also to be Shari’ah compliant. Hence it is timely to examine the impact of service quality on customer satisfaction as well as customer loyalty and retention in Islamic banks in Malaysia with the increase emphasis of shariah governance and compliance in the banking industry. A purposive sample of 339 Islamic bank customers with Islamic bank accounts was selected for the purpose of this study. Due to the institutional impediments in direct distribution of survey questionnaires, an online survey to selected respondents was administered. The survey sample includes respondents who are customers with banking accounts of several prominent Islamic banks in Malaysia. The service quality dimensions examined are tangibility, reliability, empathy and responsiveness and analysis of the significant effects of these dimensions on customer satisfaction, customer loyalty and customer retention. Among all these, except tangibility dimension, show significant impact on customer satisfaction and higher impact on customer loyalty and customer retention. In addition, this is an attempt to analyze the impact of service quality on customer satisfaction, customer loyalty and customer retention. This implies that customer utility experience is expected to result in a longer term relationship with Islamic banks.